Pinewood pyrolysis occurs at lower temperatures following treatment with choline-amino acid ionic liquids. (15th January 2019) - Brunner, Manuel; Li, Hua; Zhang, Zhezi; Zhang, Dongke; Atkin, Rob
Graphical abstract: Highlights: Interactions between choline-amino acid ionic liquids and pinewood has been probed. Cholinium arginate solubilises the greatest mass of pinewood at 19%. Cholinium glycinate solubilises only 9% of the pinewood, but leads to decomposition at significantly lower temperatures. Abstract: Pinewoods are the dominant species in Australian softwood plantations and an important source of renewable lignocellulosic biomass. This work examines interactions between cholinium amino acid (Ch[AA]) ionic liquid (IL) – Water mixtures and pinewood. The Ch[AA] ILs employed were cholinium arginate (Ch[Arg]), cholinium glycinate (Ch[Gly]), and cholinium aspartate (Ch[Asp]), with water contents between 32 and 42 wt%. Pinewood and Ch[AA] ILs were mixed at 90 °C for all samples, and also 120 °C for Ch[Arg], as it dissolved the most biomass at 90 °C. Thermogravimetric analysis (TGA), scanning electron microscopy (SEM), x-ray diffraction (XRD), and compositional (CHNS) analysis were performed on the raw and treated biomass samples to reveal the changes in physical and chemical properties. While Ch[Arg] solubilised the greatest mass of biomass during treatment, the most pronounced changes in decomposition properties was obtained using Ch[Gly]. The TGA analysis revealed the maximum in the derivative weight loss data shifted to lower temperatures by 29 °C.